Combined morphological and multi-omics analyses to reveal the developmental mechanism of Zanthoxylum bungeanum prickles - Su, Kexing; Sun, Jiaqian; Han, Jun; Zheng, Tao; Sun, Bingyin; Liu, Shuming (Frontiers in Plant Science, 2022)
Zanthoxylum bungeanum Maxim. as an important economic forest, its epidermis bears prickles which complicate the harvesting process and increase the labor costs. To explore the developmental mechanism of prickles, three varieties of Zanthoxylum bungeanum (PZB, SZB, GSZB) were selected for morphological and multi-omics analyses. The absorption spectra of prickles and stems were detected using Fourier-transform infrared spectroscopy (FTIR), and they were found different at 1617 cm-1, 1110 cm-1, 3319 cm-1 and 1999 cm-1. The morphology of prickles and stems were observed using light microscopy and transmission electron microscopy (TEM). The growth direction of cells on the prickle side and stem side were perpendicular to each other, and there was a resembling abscission zone (RAZ) between them. The vacuolar deposits of prickle cells were much more than stem cells, indicating that the lignification degree of prickles was higher than stems. In addition, 9 candidate genes (ZbYABBY2, ZbYABBY1, ZbYABBY5, ZbWRKY, ZbLOG5, ZbAZG2, ZbGh16, ZbIAA33, ZbGh16X1) were screened out and validated base on transcriptome and qRT-PCA. As well as, 30 key metabolites were found related to prickle development base on metabolome analysis. Among them, 4-hydroxy-2-oxopentanoate, trans-2-hydroxy-cinnamate, trans-cinnamate, polyhydroxy-fatty acid, 10,16-dihydroxypalmitate, cinnamic acid were related to the biosynthesis of cutin, suberine and wax. Indole-3-acetate, tryptamine, anthranilate, fromylanthranilate, N6-(delta2-isopentenyl)-adenine were related to plant hormone signal transduction. Generally, this is the first study to reveal the developmental mechanism of prickles. The results of this study lay the foundation for the breeding of non-prickle Zanthoxylum bungeanum.